Study Of Interaktif Recognition Letter and Number For Children With Computer Multimedia - Retno .; Margono .; Bambang Eka Purnama (SPEED - Sentra Penelitian Engineering dan Edukasi, 2008)
ABSTRACT By using computer, children can play with get many good matter, so can developing  potency in a child, good that Ianguage potency, artistic and intellegence of child. In consequence shall be given trainings to child for the development of its ability with things took a fancy to children. Matter which need to be tried with application programs having the character of " edutainment" that is solidarity between entertainment and education, because the application program have ability grow to develop child imagination and creativity and also train nerve motorik of child. Pursuant to background hence formula of this problem is there is no him study of recognition number and letter for child with things took a fancy to children with a computer media. And how design and make study of interaktif able to teach children learn to calculate and read by using concept of edutainment made by interaktif. In making of this research, writer limit and study about making of study interaktif recognition of number and letter for the children of age 4-6 year. Writer perform a data collecting by raising question to children with age 4 to 6 year. Afterwards making of interesting desaign for children and application it by using Macromedia Director 8.0 Later then process direct test-drive to responder to get input about study of interaktif for children to use computer of multimedia which have been made.This study interaktif recognition of number and letter is study giving a education for the children of age 4-6 year in recognizing letter and comprehend calculation of number at the same time introducing them at computer. With fitur animation can make children interest to study number and letter. And use this need instruction and tuition from her parent or adult. Keyword : Study Of Interaktif Recognition Letter and Number